Peramalan Produksi Kelapa Sawit Menggunakan Jaringan Syaraf Tiruan Dengan Metode Backpropagation (Studi Kasus PT.Sandabi Indah Lestari) - Retiana Fadma Pertiwi Sinaga; Budi Darma Setiawan; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
One of the Big Private Plantation companies in Indonesia is PT. Sandabi Indah Lestari located in Bengkulu Province. PT.Sandabi Indah Lestari designs a budget every year to spend on production process conducted once every week. Each production process of course requires a separate cost, if the production can not change production costs, the company will incur losses. Therefore, it is necessary to forecast the output of palm oil production to be a reference for the production results remain stable or even increased. Forecasting results can later be used by the company to improve production and do not lose from budget planning targets that have been made. This research uses backpropagation method combined with nguyen widrow algorithm. From the test results with the number of 260 data train, the amount of test data 12 test data, the value of learning rate 0.4, the number of hidden layer 5 neurons, the error limit of 0.001, and the maximum iteration of 900 yields MAPE (Mean Absolute Percentage Error) value of 10,0047 %.